Generic redescription of Chinaria Davis, 1934 with a new cicada genus for the Dominican species previously assigned to the genus (Hemiptera: Cicadidae: Cicadinae: Zammarini) - Sanborn, Allen F. (Zootaxa, 2024)
A complete description of the cicada genus Chinaria Davis, 1934 is provided. The genus Heatharia n. gen. is described and illustrated for the Dominican species originally classified in Chinaria. The new genus is supported through morphological, biogeographical, and genetic evidence. Heatharia vivianae (Ramos, 1983) n. comb. is reassigned as the only species of the new genus. The first record of Odopoea suffusa (Walker, 1850) is provided for Haiti.